Optimizing the Process of Countering the Corruption of Tax Regulations under the Conditions of the Coronavirus Infection Pandemic - V. V. Firsov (Теоретическая и прикладная юриспруденция)
The present article is devoted to the analysis of corruption in the optimization of the tax laws and regulations. An attempt is made to analyze the limits of the admissibility of anti-corruption regulation of tax legal relations by subordinate legal acts. With the development of public relations, there is an increase, alas, in illegal acts. Corruption is no exception. Thus, its variety is corruption in the field of tax legislation, where corruption poses a threat to the economic security of the country, distorting the system of fiscal state power and management, disrupting market reforms and, accordingly, distorting the law-abiding legal consciousness of Russian society. Individual representatives of the legislative branches of government sometimes use their powers and the rights entrusted to them for personal criminal gain. By its very nature, the verification of the law for compliance with the Constitution of the Russian Federation is addressed to the knowledge of the normative forming grounds of law, followed by a particular economic meaning. The inseparable link between all elements of the legal system and the Constitution of the Russian Federation, supported by the activities of the Constitutional Court of the Russian Federation, does not allow the main priority of the legal social state — constitutional legality, including the optimization of the process of combating corruption, tax rulemaking in the context of the coronavirus pandemic, to disappear.